The Song of the Bells: First World War Songs in Romanian Tradition - Sabina Ispas (Studia Ethnologica Pragensia, 2023)
The centenary of the end of the Great War, the War of Nations, First World War, has multiple meanings, expressed concretely in European geopolitics. This event, which occupies an exceptional position in the history of the last century, has led to the appearance in folklore of an epic-lyric category with specific features, Songs of Military and War. In Romanian folk literature, there is an impressive number of such poetic texts. Along with other categories of war memories — personal histories, family histories, and the versified songs of the soldiers, they make up a unitary and rich chapter of war folklore. In the occupied areas there were requisitions of all kinds: clothes, food, animals, objects, and especially bronze objects for the manufacture of weapons. Such a requisition took place in the village of Poiana Sibiului in Transylvania in which the villagers attended a funeral-like ceremony bidding farewell to the bells in song, ‘The Song of the Bells’.